Estimación del Potencial Aurífero del depósito de la Mina Mollopongo Código Catastral 023, en el Cantón Camilo Ponce Enríquez y Provincia Azuay. - Aranda Torres., Lady Nathaly (2024)
The current research work called “Estimation of the Gold Potential of the Mollopongo Mine Deposit Cadastral Code 023, in the Canton Camilo Ponce Enríquez, Province of Azuay” focuses on the geological characterization of the Mollopongo mining area cadastral code 023, with 60 hectares. This research was carried out based on the interpretation and geoprocessing of the information from 24 boreholes provided by the company Grupo Bonanza. This information contributed to the characterization of the geological elements of the study area in which it was determined that the predominant rock is andesite, as well as its geometry, structures such as micro-faults, fractures, veinlets and its mineralogy such as quartz pyrite pyrrhotite, which are main indicators of porphyry deposit. With the previously analyzed interpretation, it was possible to proceed to a three-dimensional modeling of the deposit to give way to the calculation of the resource estimate, in which the block method was used due to its capacity to better indicate the spatial distribution of mineralization with more detail and precision, since in this model the mineralized body is divided into a three-dimensional matrix of small blocks, which contain important information about the mineral grade, volume and density. In this way, the results of this titling work will help to comprehensively understand the geology of the study area, as well as the geometry of the deposit and its gold potential, which will give way to future stages of exploitation. Keywords: Geological characterization, three-dimensional modeling, gold potential, resource estimation.